2017
DOI: 10.1038/s41598-017-01465-1
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory threshold and odor discrimination ability in children – evaluation of a modified “Sniffin’ Sticks” test

Abstract: The clinical diagnostics of olfactory dysfunction in children turns out to be challenging due to low attention span, insufficient linguistic development and lack of odor experiences. Several smell tests have been developed for adults. Most of these examinations take a relatively long time and require a high level of concentration. Therefore, the aim of the current study was to evaluate an odor discrimination and olfactory threshold test using the frequently used “Sniffin’ Sticks” in children and adolescents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…Therefore, age-appropriate olfactory tests are necessary and have indeed been developed [9, 11, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, age-appropriate olfactory tests are necessary and have indeed been developed [9, 11, 22]. …”
Section: Discussionmentioning
confidence: 99%
“…This is in the same line with previous studies demonstrating age-related increases in children's IS [14,17,18,27]. However, in the current study,although we observed a tendency toward a better threshold score with age, differences did not reach statistical significance.A previous study evaluated olfactory threshold in children using a modified "Sniffin' Sticks" threshold test [20]. They reported an increase in threshold scores with age.…”
Section: Discussionmentioning
confidence: 99%
“…However, smell loss patients were initially evaluated with the Smell Wheel test [16], which has no normative/reference values published to date. Therefore the difference between partial or total loss of smell [13] and the "Sniffin' Sticks" olfactory threshold test [20] seem suitable and reliable for children and adolescents. However, these tests were developed in a specific country with country specific odors that may not be suitable for Spanish children.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we decided to only administer the odor discrimination test. Gellrich et al (2017) recently evaluated the discrimination task of the sniffin' stick test in a children sample (ages 5-17 years) and found sufficient retest reliability (r = 0.69).…”
Section: Materials and Proceduresmentioning
confidence: 99%